Financial guarantees that enable public-private infrastructure projects in risky developing market environments - Botha, Dewald Pieter (My University, 2019)
The growing need for infrastructure development in sub-Saharan Africa requires increased levels of private investment through public-private partnerships. These investments rely on financial guarantees to ensure that risks are appropriately allocated and managed. Governments in sub-Saharan Africa are not able to finance infrastructure projects and deal with the associated risks in order to promote infrastructure development on their own. The purpose of this research is to determine how significant the financial guarantees’ impact on commercial, political and environmental risks associated with infrastructure development is, compared to government guarantees. Expert opinions were combined with prior research and existing literature to develop fuzzy cognitive maps representing the relationships between financial guarantees and infrastructure risks. While government guarantees outperformed all of the financial guarantees in mitigating infrastructure risks in general, the alternative financial guarantees performed better at mitigating certain specific infrastructure risks. This study confirmed that financial guarantees alone are unable to negate or mitigate infrastructure risks. A combination of government guarantees and financial guarantees will vastly improve the risk-cover presented, increasing the level of private investment participation in infrastructure development in sub-Saharan Africa.
MBA
Keywords: Public-private sector cooperation -- South Africa. Infrastructure (Economics) -- South Africa.